Ontology and gnoseology of capitalism in isaak illich rubin: “essays on marxist theory of value” - Armesilla Conde, Santiago Javier (Nómadas. Critical Journal of Social and Juridical Sciences, 2017)
This concise essay attempts to show why Isaak Illich Rubin is, until today, the best interpreter, commentator and developer of The Capital of Karl Marx, understanding Marx’s work as an ontology and a gnoseology of the capitalist economic system. To do this, we analyze the relations existing between Marx, Rubin and the theory of science of the Spanish Marxist philosopher Gustavo Bueno. In this way, we can interpret the work “Essays on Marxist theory of value” also as an ontology and a gnoseology of capitalism.